Relasi Antara Tingkat Konflik di Dunia Islam Dengan Setting Geografi Politik: Studi Kasus Konflik di Kawasan Timur Tengah - Surwandono Surwandono (Jurnal Hubungan Internasional, 2013)
The main problem in the Muslim world is a conflict among the Islamic community, and other community involvement in the problem. Middle East as a region that represents a typical Islamic region have these problems, nearly a century of conflicting the Middle East experiencing extreme dynamics. This research is a type of qualitative research, and data collection techniques based on secondary data. To test the validity of data used method Triangle Truth Categorize the conflict, the author uses three levels of conflict; debate, games, and wars. By using this category, the conflict in the Middle East shows a variety of symptoms. Conflict based on religion and the sacred and strategic giving a large space for the birth of the conflict in the wars.